Structural and Electrochemical Studies of La2O3 Coated LiCoO2 Particles. Issue 3 (2nd July 2020) - Rao, Bhuvanagiri Nageswara; Narsimulu, Daulatabad; Rao, Annavarapu Tirupathi; Madhusudhanrao, Vallabhaneni; Satyanarayana, Nallani
Abstract : Nanocrystalline LiCoO2 particles have been surface modified with La2 O3 by a simple and cost effective resin coating process. The synthesized pure and La2 O3 coated samples were characterized by thermogravimetric analysis / differential scanning calorimetry (TGA/DSC), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques. XRD studies revealed that the presence of La2 O3 coating over LiCoO2 particles did not affect the original layer structure of pure LiCoO2 . Also, no extra peak was detected for La2 O3 phase. FTIR results confirmed the structural co-ordination of the samples. Also, the shifting and broadening of IR peaks corresponding to LiCoO2 confirmed the presence of IR peaks of La2 O3 . TEM image showed the formation of interconnected small nanoparticle subunits structure for LiCoO2 . TEM image also showed the presence of thin La2 O3 layer over LiCoO2  particles. The cyclic voltammetry studies revealed that the La2 O3 coated LiCoO2 particles exhibited reversible redox peaks with slight increase in peak intensity and peak area compared to pure LiCoO2 . It indicates an improved charge storage capacity of La2 O3 coated LiCoO2 sample compared to pure LiCoO2 sample. GRAPHICAL ABSTRACT: